Effects of recombinant human growth hormone in severe neurosurgical patients: A single center, retrospective study. - Xixian Liao; Haorun Huang; Binghui Qiu; Jiaping Chen; An Zhang; Haoxin Liang; Chuanping Huang; Fen Mei; Jian Mao; Fan Liu; Ming Jin; Xiaojie Peng; et al. (PLoS ONE)
Purpose To explore the effects of recombinant human growth hormone (r-hGH) on inflammatory mediators, immune cells and prognosis in severe neurosurgical patients. Methods From August 2020 to June 2021, a total of 236 patients who admitted to the neurosurgical intensive care unit (NSICU) were retrospectively analyzed. The patients were divided into GH group (97 cases) and nGH group (139 cases) according to whether they received r-hGH treatment. Parameters including CD4+ T cell counts, inflammatory mediators and prognosis were recorded and assessed. Results The results showed that the cure time of pneumonia and intracranial infection in GH group patients was significantly shorter than in the nGH group (24.25 ± 4.89 days and 21.33 ± 1.53 days versus 29.13 ± 7.43 days and 25.17 ± 2.32 days, respectively). However, there was no significant difference in GOS scores between two groups (31.96% ≤ 3 and 68.04% > 3 vs 39.57% ≤ 3 and 60.43% > 3) (P = 0.232). Furthermore, the number of CD4+ T cells and CD8+ T cells in the GH group showed a significant upward trend. Last but not least, significant differences were also observed in IL-6 and IL-10 levels between two groups at days 1, 3, and 7. Conclusion The application of r-hGH in severe neurosurgical patients was effective in increasing the number of CD4+ T cells, down-regulating inflammatory mediators, shortening the cure time of pneumonia, intracranial infections and urinary tract infections, and improving patients' prognosis.